Key questions in thoracic surgery - Moorjani, Narain; Viola, Nicola; Walker, William S. (William Stanley) (Tfm Pub., 2016)
Key Questions in Thoracic Surgery will systematically cover all the main topics involved in the current practice of a thoracic surgeon. Each chapter will be structured to include etiology, pathophysiology, clinical features, indications for surgery, peri-operative management, surgical options and postoperative care. Possible complications will be discussed and the results of current practice presented.